Toxicity of topical ophthalmic anesthetics. (August 2013) - Patel, Michelle; Fraunfelder, Frederick W
<x xml:space="preserve">Abstract</x> Introduction: Topical ocular anesthetics are generally well tolerated in clinical settings but have great potential for abuse if used by patients at home. This abuse can lead to significant ocular complications. Topical ocular anesthetic abuse can lead to superficial punctate keratitis, persistent epithelial defects, stromal/ring infiltrates, corneal edema, endothelial damage and ocular inflammation, even when used in a dilute concentration. Patient characteristics may include a healthcare association and/or psychiatric illness. In these instances, patients often do not admit to anesthetic use and are often initially treated for acanthamoeba keratitis. Local anesthetics are thought to cause direct toxicity to the corneal epithelium, stroma and endothelium. This in turn may lead to release of antigens and from there an inflammatory response in the form of infiltrate and edema. It is thought that preservatives in anesthetics may play a further role in toxicity. Areas covered: The authors provide a brief history on topical ocular anesthetics and review the most recent literature on reported ocular toxicities of topical anesthetics. Expert opinion: Practitioners must maintain high suspicion for topical ocular anesthetic abuse to identify it early. Topical ocular anesthetic abuse is often misdiagnosed as acanthamoeba keratitis. Early identification is one of the most important factors for a successful outcome. It is also imperative to give proper alternative pain control to avoid topical anesthetic abuse.